Circulating microRNA-122-5p correlates with improvement in left-ventricular function after transcatheter aortic valve replacement and regulates viability of cardiomyocytes via extracellular vesicles. (14th October 2021) - Hosen, M R; Xiang, X U; Goody, P R; Zietzer, A; Niepmann, S T; Zimmer, S; Sinning, J M; Sadeghat, A; Tiyerili, V; Latz, E; Werner, N; Nickenig, G; et al.
Abstract: : Transcatheter aortic valve replacement (TAVR) is a well-established treatment option for high- and intermediate-risk patients with severe symptomatic aortic valve stenosis (AVS). However, a specific role for circulating microRNAs (miRNAs) in the improvement of cardiac function for patients after TAVR has not yet been investigated. Herein, we generally explored the differential expression of miRNAs in circulating extracellular vesicles (EV-miRNAs) in patients after TAVR and, in particular, the novel role of circulating miR-122-5p in cardiomyocytes. Circulating EV-associated miRNAs were investigated by using an unbiased Taqman-based human miR array. Several EV-miRNAs (miR-122-5p, miR-26a, miR-192, miR-483-5p, miR-720, miR-885-5p, and miR-1274) were significantly deregulated in aortic stenosis patients at day seven after TAVR in comparison to the pre-procedural levels in patients without LVEF-improvement. The higher levels of miR-122 were negatively correlated with LVEF improvement at both day seven (r=−0.264 and p=0.015) and at six months (r=−0.328 and p=0.0018) after TAVR. At the three-year follow-up, patients with a higher level of miR-122-5p displayed significantly increased cardiovascular mortality (p=0.03). By utilization of patient-derived samples and a murine aortic-stenosis model, we observed that the expression of miR-122-5p correlates negatively with cardiac function, which is associated with LVEF. Graded wire-injury-induced aortic-valve-stenotic mice demonstrated a higher level of miR-122-5p, which was related to cardiomyocyte dysfunction. Murine ex vivo experiments revealed that miR-122-5p is highly enriched in endothelial cells in comparison to cardiomyocytes. Co-culture experiments with endothelial cells and cardiomyocytes, copy-number analysis, fluorescence microscopy with Cy3-labeled miR-122-5p demonstrated that miR-122-5p can be shuttled via large extracellular vesicles from endothelial cells into cardiomyocytes. Gain- and loss-of-function experiments suggested that EV-mediated shuttling of miR-122-5p increases the level of miR-122-5p in recipient cardiomyocytes and regulates viability of the cardiomyocytes. In silico prediction and mass spectrometry were used to search for binding partners of miR-122-5p. Mechanistically, miR pulldown, electrophoretic mobility shift assay, and RNA immunoprecipitation confirmed that miR-122-5p interacts with an RNA-binding protein, hnRNPU, in a sequence-specific manner to encapsulate miR-122-5p into large EVs. Upon shuttling into recipient cells, miR-122-5p negatively regulates the expression of the anti-apoptotic gene BCL2, by binding to its 3' untranslated region to regulate its translation, and thereby decreasing the viability of target cardiomyocytes. Increased levels of circulating pro-apoptotic EV-incorporated miR-122-5p is associated with reduced LVEF after TAVR. Extracellular vesicular shuttling of miR-122-5p regulates the viability and apoptosis of cardiomyocytes in a Bcl2-dependent manner. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): German Research Foundation (DFG); German Society of Cardiology (DGK)